2011
DOI: 10.1136/oem.2010.064220
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and genetics increase risk of beryllium sensitisation and chronic beryllium disease in the nuclear weapons industry

Abstract: Objectives Beryllium sensitisation (BeS) and chronic beryllium disease (CBD) are caused by exposure to beryllium with susceptibility affected by at least one well-studied genetic host factor, a glutamic acid residue at position 69 (E69) of the HLA-DPβ chain (DPβE69). However, the nature of the relationship between exposure and carriage of the DPβE69 genotype has not been well studied. The goal of this study was to determine the relationship between DPβE69 and exposure in BeS and CBD. Methods Current and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Their numbers of people studied were small (19 persons with CBD and 34 who were beryllium exposed), so their study was limited in what relationships they could evaluate. More recently, Van Dyke et al (17, 18) found this same relationship in a larger population-based study even after taking into account the increased risk associated with exposure.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Their numbers of people studied were small (19 persons with CBD and 34 who were beryllium exposed), so their study was limited in what relationships they could evaluate. More recently, Van Dyke et al (17, 18) found this same relationship in a larger population-based study even after taking into account the increased risk associated with exposure.…”
supporting
confidence: 53%
“…All study subjects were white. Some of the subjects in this study were included in prior smaller studies of CBD and BeS risk related to E69 (8, 10, 17, 18), although some subjects were only included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Suggested occupational risk factors include metal working industries (from an ecological study in Switzerland)4 and exposure to insecticides 2. No clear gene–environmental interaction has been reported for sarcoidosis, contrasting strongly with the highly elevated risk of chronic beryllium disease (CBD) in those with a glutamic acid residue coded for in codon 69 (Glu69) in the HLA-DPB1 gene 5. Given that CBD is clinically and pathologically indistinguishable from sarcoidosis, it is reasonable to hypothesise that genetic variation in the presentation of one or more (as yet unknown) antigens may be causal also in sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“…The health effects of exposure have largely been investigated in the USA in the nuclear industry 5. Importantly, no clear dose–response relationship has been found between exposure and CBD, although there is an assumption that sensitisation to beryllium depends on intensity of exposure and perhaps also duration and/or latency 6.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Van Dyke and colleagues have shown that the supra-typic genetic marker, HLA-DPB1(E69), has an additive and independent contribution with beryllium exposure to cell-mediated beryllium sensitisation and chronic beryllium disease in a cohort at a US nuclear weapons plant 1. This finding of statistical independence between required beryllium exposure and genetic characteristics is quantitatively consistent with an earlier finding in a small beryllia ceramics operation,2 and is extended by a concurrent publication in a second, larger nuclear weapons plant population 3.…”
mentioning
confidence: 99%